Costo de ventas versus los ingresos del almacén Montoya - Fernandez Loor, Rosaura Ninoska (2018)
The present case of investigation is carried out in order to make a analysis of cost of sales versus the income of the Montoya warehouse. This entity started its activities on June 12, 1980 in the city of Vinces today This business is being managed by Mr. Edward Montoya and is located in the Calle 10 de Agosto and Balzar, where there is a high commercial traffic in the area. Almacén Montoya is an entity that is dedicated to the trade of fabrics, both retail as the wholesale, in addition to providing the technical advice service in each acquisition of goods addressed to the final consumer and other customers who He has this entity as a courtesy. The company has liquidity problems (Annex 3) and a level of costs that mark the financial inefficiency and profits are low, aims to achieve a recovery by increasing the volume of inventory in order to cover a larger portion of the market, for this purpose the warehouse holds a stock considerable, with an average inventory method.